The role of medical simulation curriculum in developing acute care clinical competence in undergraduate medical students in South Africa - Jansen, Marvin Jeffrey (Department of Health Sciences Education, 2022)
The study aim was to explore the role, including the limits and possibilities, of medical simulation as a pedagogical method in an undergraduate acute care clinical skills curriculum within a South African tertiary education environment. The study consisted of two phases. During phase one, I conducted a modified Delphi study to identify the acute care clinical skills competencies undergraduate medical students need to acquire to prepare them, in the role as newly qualified clinicians, for managing acute care cases within a South African in-hospital environment. Phase two explored what acute care clinical competencies would lend themselves to a medical simulation modality within a South African tertiary education environment, as well as exploring the role, the limits and possibilities of medical simulation as an educational modality in developing acute care clinical skills curriculum within a South African tertiary education environment. The data was collected through Focus Group Discussion (FGD) and semi-structured interviews with simulation experts within South Africa. The findings of the modified Delphi study contributed to developing a comprehensive list of undergraduate acute care clinical skills competencies, previously unavailable, for SA. The value of engaging with medical practitioners at the forefront of societal engagement such as practising medical practitioners, who on a day-to-day basis are exposed to the healthcare needs of society, became evident. Having empirically established a comprehensive set of acute care competencies for SA undergraduate medical education, phase 2 sought to identify the simulation modality/modalities that these competences would lend themselves to. Thereafter, pesent the SimSMART framework for curriculum developers exploring the possibility of implementing simulation as pedagogy in their context. The findings were significant as they provided curriculum developers with contextually relevant literature to consider which competencies would best be suited to medical simulation as pedagogy, which is particularly important when considering the resource constraints within developing world contexts. The findings provided valuable insights into complex contextual issues such as the effects of the Apartheid legacy on teaching within health sciences, communication, and social inequality.